Modern trends of agribusiness development in terms of economic area’s globalization. (Journal of Economic Research & Business Administration, 2015)
The article reveals the laws of agribusiness development in a globalized economic space. Modern trends in the development of agribusiness are shown. Characteristic trends in the development of agribusiness are shown. The problems of maintaining the level of fi nancial resources, agricultural enterprises and government intervention in the production and trade of agricultural commodities through fi nancing and subsidizing the production of many agricultural products is studied in the research paper. The features of the global food market are studies. They can be characterized by the features of an industrialized economy: a high level of technology, organization of marketing activities of agricultural fi rms, including a powerful advertising, the concentration of capital, competition among producers, focused on user requests. The share of agriculture in GNP and the GDP of several countries of the world is analyzed; the structure of global grain crops production was shown using complex criteria, including ratings and evaluation of leading economic agencies, as well as foreign experts’ opinions.
Keywords: globalization; economic space; agribusiness; agro-industrial system